Tranformasi Digital Melalui Implementasi E-Government Pada Organisasi Sektor Publik - Muhammad Taufiq Hidayat; Yohanes Sri Guntur (Majalah Ekonomi, 2025)
Objective – This study aims to analyze how digital transformation and the implementation of e-government affect efficiency, transparency, and accountability in public services in Indonesia. In addition, this study aims to identify gaps in the existing literature and provide recommendations for the development of studies and strategies for future digital transformation of government. Methodology – This study uses a literature study method with qualitative analysis of researchers on the topic of digital transformation through the implementation of E-Government in various regions and government institutions in Indonesia. This study examined 54 scientific articles in Indonesia that discussed innovations, challenges, and the impact of e-government on governance and public services. Findings – The results of the study show that the implementation of e-government in various regions of Indonesia has increased the efficiency, transparency, and accountability of public services, although they are still faced with limited infrastructure and low digital literacy of the community. The government's digital transformation does not only depend on technology, but is also influenced by social, political, and organizational cultural factors that require bureaucratic reform and improvement of apparatus competence. Active community participation and cross-sector policy synergy are the keys to the successful implementation of inclusive and sustainable digital government. This study also reveals the need for theoretical approaches and strategies for human resource capacity building and revitalization of organizational values to face structural challenges and improve the quality of digital public services. Limitations – This study focused on a literature analysis so the results are highly dependent on the data and context of the published research. Further research is needed for empirical exploration and evaluation of the implementation of e-government directly. Practical Implications – Governments and stakeholders can use the results of this research as a basis for formulating inclusive digital policies, strengthening the capacity of state civil servants, and fostering cross-sector collaboration for successful digital transformation in the public sector. Authenticity – This study contributes in the form of a comprehensive synthesis of the development of e-government in Indonesia with a focus on technical, institutional, and social aspects, as well as the challenges faced in achieving more efficient, transparent, and sustainable governance.